Pengaruh Penggunaan Pengenyal Alami Glukomanan terhadap Kualitas Fisik dan Daya Terima Kamaboko Ikan Lele Dumbo (Clarias garipenus) - Dhian Priyan Raga; Alsuhendra Alsuhendra; Rusilanti Rusilanti (Student Research Journal, 2024)
Kamaboko is a processed fish product from Japan which is in gel form, is chewy and elastic (Ilma et al, 2019). Kamaboko itself is a dish made from fish that is specially processed to produce a chewy texture and delicious taste. The process of making kamaboko involves selecting high quality fish, grinding the fish meat, mixing it with certain additional ingredients, and cooking using the steam or steam method. African catfish is a type of freshwater fish that is widely cultivated by the community. Catfish is a source of animal protein that is affordable and has high nutritional content with a protein content of 18.7% (Djonu, Nursyam et al., 2022). Compared with the protein value of cod surimi, 100g of cod surimi produces 18g or around 18% protein. Meanwhile, 100g of haddock fish surimi contains 20g or around 18% protein. After carrying out these two test stages, the results of the organoleptic test on consumer acceptability were calculated through hypothesis testing using the Friedman test. If the results of the Friedman test state that it rejects H0, which means it accepts H1, then the Tuckey test calculation will continue to determine the best group from the three treatments. To test physical quality, use the ANOVA test. If the results of the anova test state that it rejects H0, which means it accepts H1, then it will continue with the Duncaan test calculation to determine the best group from the three treatments. The results of this research were obtained in two stages. The first stage was a validation test carried out on 5 expert panelists, namely lecturers from the Culinary Education Study Program and continued with the second stage, namely an organoleptic test on consumer acceptability carried out on 30 somewhat trained panelists who were Pend students. Jakarta State University Culinary Management.